Aegilops tauschii Coss. molecular phylogeny in comparison with proteins electrophoretic polymorphism - Dudnikov, Alexander J. (Acta Biologica Sibirica, 2023)
In the case of Aegilops tauschii the comparison of intraspecies molecular phylogeny based on DNA sequences of nuclear gene Got2 with electrophoretic polymorphism of allozymes and hystone H1 proteins is actually a comparison of the one detailed phylogenetic tree with a set of low resolution trees. It could help to understand peculiarities of the species evolutionary history and role of cross-pollination in it. Proteins polymorphism patterns rather satisfactory corresponded to Got2 DNA tree. Electrophoretic polymorphism of essentially polymorphic in Ae. tauschii subsp. strangulata protein encoding loci considered (Ak, Est2, Got1, Got3, Hst2, Hst3) and essentially polymorphic in Ae. tauschii subsp. tauschii locus Fdp displayed correspondence with the molecular phylogenetic tree: each allele was common or predominant on some branches of the tree and rare or absent on the other. In contrast, alleles of Cat2 locus, Cat235 and Cat2140, were “scattered” sporadically through Ae. tauschii subsp. tauschii branches on phylogenetic tree. Also in Ae. tauschii subsp. tauschii a set of different extremely rare allozyme alleles, Acph4113, Aco2110, Mdh1113, Nadhd188, was found among three out of four accessions belonging to one of the relict clades of this subspecies on the molecular phylogenetic tree. The data obtained displayed that subsp. tauschii, now being relatively less polymorphic than subsp. strangulata, in ancient times had good opportunities for genetic exchange between its different phylogenetic lineages, all but one of which are relicts in present time. And the patterns of Hst3977 allele occurrences indicated cross-pollination between subsp. tauschii and subsp. strangulata.